DOP27 Disease activity patterns in the first 5 years after diagnosis in children with Crohn's disease: a population-based study. (30th January 2023) - Distante, M; Rotulo, S; Ranalli, M; Pedace, E; Lionetti, P; Arrigo, S; Alvisi, P; Miele, E; Martinelli, M; Zuin, G; Bramuzzo, M; Cananzi, M; et al.
Abstract: Background: This study aimed to define clusters of disease activity and prognostic factors of the disease course in a well-characterized cohort of children with Crohn's disease (CD). Methods: All patients with CD identified from the SIGENP IBD registry with a follow-up of at least 5 years and a 6-monthly evaluation were included. Active disease was defined for each yearly semester as follows: clinical activity (wPCDAI≥12, 5 or MINI index ≥8), need for treatment escalation, hospitalization, or surgery, active disease on endoscopy (SES-CD >3) or imaging. Formula-based clusters were generated based on previously published patterns in adults 1 . Prediction models were created based on clinical, surgical, endoscopic, and laboratory findings at diagnosis and at 6-month follow-up. Results: Data from 332 patients were analyzed. Ninety-six (29%) had a quiescent course; 52 (16%) and 34 (10%) had a moderate-to-severe chronically active and chronic intermittent disease; 107 (32%) and 43 (13%) had an active disease in the first two years after diagnosis and remission thereafter and the opposite course, respectively. Overall, 129 (39%) children presented with an active disease at 5 years of follow-up, with no patient off-therapy. Surgery at the time of diagnosis was significantly associated with a quiescent course [OR 10.05 (CI 3, 05-25, 22), p 0.0005], while growth impairment at the diagnosis and moderate-severe activity requiring corticosteroids at 6 months were inversely related to the quiescent group [OR 0.48 (CI 0, 27-0, 81) p 0.007 and OR 0.35 (CI 0, 16-0, 71) p 0.005, respectively]. Perianal involvement at diagnosis and moderate-severe activity at 6 months positively correlated with disease progression (i.e., B1 to B2/B3) at follow-up [OR 2.55 (CI 1, 05-6, 07) p<0.04 and OR 3.85 (CI 1, 20-12, 85) p 0.02]. Seventy-three patients (22%) required surgery, of which 31 (43%) in the first 6 months after diagnosis. Conclusion: Approximately one-third of our cohort of children with CD had a quiescent course during the first five years after diagnosis. In contrast, more than one-third of the patients had a chronically or intermittently active disease during the entire follow-up, or an initial remission followed by a persistent activity. Surgery at the time of diagnosis, mild disease onset without growth impairment, and lower disease activity without corticosteroid use in the first six months after diagnosis predicted a quiescent course over time. 1. Wintjens D., Bergey F., Saccenti E. et al. Disease activity patterns of Crohn's disease in the first ten years after diagnosis in the population-based IBD South Limbrug Cohort. J Crohns Colitis. 2021; 15 (3):391-400.